2020
DOI: 10.1093/geroni/igaa057.3414
|View full text |Cite
|
Sign up to set email alerts
|

#BoomerRemover: COVID-19, Ageism, and the Intergenerational Twitter Response

Abstract: In March 2020, COVID-19 was declared a pandemic and frequently presented as a virus primarily affecting older adults. News headlines led with statements such as, “Coronavirus deaths are so far mostly older men” (Ramzy, 2020). Although later determined inaccurate, this perspective contributed to openly ageist views and exchanges from people around the world. On the social media platform of Twitter, #BoomerRemover was used as a hashtag to express views related to older adults, and particularly baby boomers, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…Hence, while generally construed as a negative emotion, anger can be constructive insofar as it galvanizes individuals to fix perceived injustices and take collective action (Lambert et al., 2019; Renström & Bäck, 2021). This reiterates past findings on how some Twitter users implored others not to use the hashtag #BoomerRemover when pleading for intergenerational unity (Sipocz et al., 2021; Skipper & Rose, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Hence, while generally construed as a negative emotion, anger can be constructive insofar as it galvanizes individuals to fix perceived injustices and take collective action (Lambert et al., 2019; Renström & Bäck, 2021). This reiterates past findings on how some Twitter users implored others not to use the hashtag #BoomerRemover when pleading for intergenerational unity (Sipocz et al., 2021; Skipper & Rose, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…This study analyzed discourse surrounding older adults on Twitter over a period of 11 months during the COVID‐19 crisis. In contrast to prior studies which evaluated tweets related to older adults during the pandemic (Jimenez‐Sotomayor et al., 2020; Sipocz et al., 2021; Skipper & Rose, 2021; Xiang et al., 2021), our study covered a broader time period and included search terms pertaining not just to older adults, but also to grandparents. Whereas these earlier studies discovered the presence of hostile ageism on Twitter at the start of the crisis (Jimenez‐Sotomayor et al., 2020; Sipocz et al., 2021; Skipper & Rose, 2021; Xiang et al., 2021), our findings revealed that ageism in the Twitter sphere became more nuanced as the crisis unfolded throughout 2020, with narratives centered around two main topics: the need to protect older adults (41%) as well as their vulnerability and mortality (36%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit not directly investigated from an intergroup perspective, similarly to other forms of prejudice, ageism has been explained as the result of tension between groups (North & Fiske, 2012). When the resources are scarce, intergroup conflict might arise with perceived symbolic and realistic threat increasing hostility and disputes over the resources’ allocation among groups (Sherif et al., 1961; Stephan & Stephan, 2017). While realistic threats regard tangible harms (e.g., economic power and physical or material wellbeing), symbolic threats refer to intangible harms (e.g., differences in values, morality, and norms) to the ingroup (Stephan & Stephan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Media studies prove such a modern trend, according to which, for example, a quarter of tweets "downplayed the importance of COVID-19 because it was more deadly among older people, and 14 % contained offensive content or jokes about older generations" (Jimenez-Sotomayor, Gomez-Moreno, & Soto-Perez-de-Celis, 2020). News headlines came from statements such as: "The elderly have died from coronavirus so far" (Skipper & Rose, 2020).…”
Section: Age-related Discrimination In the Social And Communication Areamentioning
confidence: 99%